1984
DOI: 10.1159/000183157
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Muscle Weakness in Uremic Patients under Continuous Ambulatory Peritoneal Dialysis

Abstract: The increasingly frequent use of continuous ambulatory peritoneal dialysis (CAPD) as substitutive therapy in terminal renal failure has induced the investigation of the advantages and disadvantages of this therapeutic modality. The effects of CAPD on pulmonary function are one of the aspects currently under study. Based on previous data suggesting the existence of extrapulmonary ventilatory restriction in uremic patients under CAPD, we have studied in these patients the respiratory muscle function as expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
3

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 5 publications
2
23
0
3
Order By: Relevance
“…Most of the patients had their catheter removed and dialysis method changed, because no success was obtained with the treatment. The main mechanical complication was early leakage (10%), which is in agreement with other studies (6,9,11,29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most of the patients had their catheter removed and dialysis method changed, because no success was obtained with the treatment. The main mechanical complication was early leakage (10%), which is in agreement with other studies (6,9,11,29).…”
Section: Discussionsupporting
confidence: 92%
“…The works by Phu et al (25) and Bazari (27) reported that intermittent PD failed to control academia, because PD impairs diaphragm mobilization, with a resulting increase in intra-abdominal pressure and reduction in pulmonary compliance and ventilation. It also causes tissue and organ hypoperfusion and maintains acidosis (29).…”
Section: Discussionmentioning
confidence: 99%
“…Gómez-Fernández et al 36 were among the first authors to report on evaluations of maximal respiratory pressures in this population. They evaluated CKF patients who underwent CAPD and found decreased MIP in patients with CKF (59.6% of predicted values), compared with controls (82.7% of predicted values).…”
Section: Discussionmentioning
confidence: 99%
“…26 The cause is unknown, but has been related to carnitine deficiency 25 , vitamin D deficiency 27 , excessive amount of parathyroid hormone 28 , aluminum toxicity 29 , and other uremic toxins. 30,31 Uremia causes atrophy of type II muscle fibers 29 and alterations in myofibrillar ATPase, with an important reduction in energy use by the muscle, in creatine phosphorylation, and its contractility.…”
Section: Discussionmentioning
confidence: 99%